Evaluation of the Implementation of ERAS Protocol in Colorectal Surgery at dr. Cipto Mangunkusumo General Hospital, Jakarta - Jeo, Wifanto S; Mazni, Yarman; Suryadi, Andre S (The New Ropanasuri Journal of Surgery, 2020)
Background: The enhanced recovery after surgery (ERAS) protocol, an evidence-based perioperative strategy, has been proven in reduces the postoperative length of stay and perioperative complications rates in colorectal surgery. The implementation of ERAS defined by 15 components. However, the evaluation of ERAS component that have been applied to the outcomes in unclear. Methods: A retrospective study was performed on 63 patients who undergone elective colorectal surgery based on ERAS protocol from January 2015 to December 2017 at Cipto Mangunkusumo Hospital. Patient characteristics, demographic, clinical findings, and length of stay (LOS) colleted from medical records. The relationship between the number of ERAS that accomplish and LOS was analyzed. Result:All patients implemented up to 11 of 15 ERAS components. The mean age of the patients was 53 years old; 46% of patients were males, and 54% were females. There were no mortality rates. The morbidity rate was 7.9%, caused by surgical site infection 1.6%, pneumonia 1.6%, and urinary retention 4,8%. The most common location for colorectal tumour and procedure were sigmoid (47,6%) and colostomy closure (25,4%). There was a relationship between the total ERAS component protocols and the average length of stay (p Conclusion: The higher number of ERAS components applied to one patient, the shorter LOS for postoperative care needed.